Radon emissions related to the granitic Precambrian shield in southern Brazil - Fianco, Ana C. B.; Roisenberg, Ari; Bonotto, Daniel Marcos [UNESP] (Taylor & Francis, 2013)
The equivalent uranium (eU) activity concentration was analysed in selected granite samples at several sites in Porto Alegre, Southern Brazil, to obtain information on the radon (222Rn) generation by the aquifer rock matrices. Radon analyses of ground water and soil samples were also performed. Several samples exhibited a dissolved 222Rn activity concentration exceeding the World Health Organization maximum limit of 100 Bq l-1. The dissolved radon content in ground waters from the Fractured Precambrian Aquifer System exhibited a direct significant correlation with the eU in the rock matrices, which is a typical result of water-rock interactions. Variation in the soil's porosity was confirmed as an important factor for 222Rn release, as expected, due to its gaseous nature. Thus, although the calcic-alkaline to alkaline Precambrian granitoid rocks of the study area are important reservoirs for underground resources, they can release high amounts of radon gas into the liquid phase. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: granitoid rocks; ground water; natural radioactivity; Porto Alegre (RS); radioactive nuclides; radon-222; soils; radon; silicon dioxide; aquifer; emission; granitoid; groundwater pollution; porosity; Precambrian; radioactivity; radon isotope; soil pollution; uranium; water-rock interaction; Brazil; chemistry; granite; radiation monitoring; soil; soil pollutant; water pollutant; Groundwater; Radiation Monitoring; Radon; Silicon Dioxide; Soil; Soil Pollutants, Radioactive; Water Pollutants, Radioactive; Porto Alegre; Rio Grande do Sul